Impacts of an Invasive N2‐Fixing Tree on Hawaiian Stream Water Quality. (19th January 2013) - Wiegner, Tracy N.; Hughes, Flint; Shizuma, Lisa M.; Bishaw, David K.; Manuel, Mark E.
Abstract N2‐fixing trees can affect stream water quality. This has been documented in temperate streams, but not in tropical ones, even though N2‐fixing trees are prevalent in the tropics. We investigated the effects of the introduced, invasive tree, Falcataria moluccana (albizia) on water quality of Hawaiian streams. Nutrient concentrations were measured in reaches above and below F. moluccana‐dominated riparian zones of four streams over 14 mo, and benthic algal nutrient limitation was examined in one stream. NO3−+NO2− concentrations were up to 600 percent higher in reaches below F. moluccana stands than in ones above them. In contrast, dissolved organic nitrogen concentrations were 24 percent lower in most reaches below F. moluccana stands, and NH4+ and particulate nitrogen concentrations were similar above and below the stands. Dissolved organic carbon concentrations were up to 30 percent lower below F. moluccana stands, but particulate carbon concentrations were similar between reaches. Total dissolved phosphorus concentrations were similar above and below F. moluccana stands, whereas H4SiO4 concentrations were higher below the stands. In the stream where benthic chlorophyll a was measured, concentrations were three times higher below the F. moluccana stand than above it. Benthic algae were co‐limited by nitrogen and phosphorus above the F. moluccana stand, and limited by phosphorus below it. These results suggest that F. moluccana's presence relieved nitrogen‐limitation and caused the benthic algae to become solely phosphorus‐limited. Overall, our results demonstrate that F. moluccana can strongly affect the chemistry and primary producers of these tropical streams.